A new IV approach for estimating the efficacy of macroprudential measures - Niklas Gadatsch; Lukas Mann; Isabel Schnabel (Sachverständigenrat zur Begutachtung der Gesamtwirtschaftlichen Entwicklung, 2017)
We propose a new identification strategy to assess the efficacy of macroprudential measures. We propose a novel instrumental variable that is based on the idea that a politically sensitive macroprudential measure is more likely to be implemented if a politically independent institution, such as a central bank, is in charge. Our results show that borrower-based macroprudential measures have had a strong and statistically significant dampening effect on credit growth in the European Union.
Keywords: 330